Nefrosis congénita con lesiones mínimas. Presentación de 2 casos. - Torres Aldrich, Hugo; Arias Fonseca, Eduardo; Llauradó Loaces, Rafael; Legrá Rodríguez, Rafael; Torres Rodríguez, Raisa (Revista Cubana de Pediatría, 2025)
Se presentan 2 pacientes con nefrosis congénita.